Can intravenous antifungal therapy be safely used in the outpatient parenteral antimicrobial therapy (OPAT) setting?. Issue 3 (22nd January 2019) - Rae, Nikolas; Kenny, Claire; Muldoon, Eavan G.
Summary: Outpatient parenteral antimicrobial therapy (OPAT) is an established treatment option for patients with a variety of infections who require a period of intravenous therapy, are clinically stable, and do not require continuous monitoring. Many patients with fungal infections require prolonged therapy due to resistance or intolerance to oral antifungal agents. Despite the widespread use of OPAT by infection specialists, antifungal agents appear infrequently used in this setting. We suggest that with appropriate patient selection, patients with fungal infections could successfully be treated on OPAT.